Effects of maternal high‐fat/high sucrose diet on hepatic lipid metabolism in rat offspring. (7th September 2020) - Ingvorsen, Camilla; Lelliott, Christopher J.; Brix, Susanne; Hellgren, Lars I.
Abstract: Maternal obesity and/or high‐fat diet during pregnancy predispose the offspring to metabolic disease. It is however unclear how pre‐natal and post‐natal exposure respectively affect the risk of hepatic steatosis and the trajectory towards non‐alcoholic steatohepatitis in the offspring. We investigate hepatic lipid metabolism and how these factors are related to metabolic outcome in new born and young rats. Rat dams were exposed to a high‐fat/high sucrose (HFHS) diet for 17 weeks prior to mating and during pregnancy. After birth, female offspring were killed and male offspring were cross‐fostered, creating four groups; Control‐born pups lactated by control (CC) or HFHS dams (CH) and HFHS‐born pups lactated by control (HC) or HFHS dams (HH). At 4 weeks of age, pups were killed and metabolic markers in plasma were assayed, together with hepatic lipid composition and expression of relevant genes. Female HFHS neonates had smaller livers at birth ( P  < .05), a reduced hepatic lipid content ( P  < .05) and altered lipid composition. The post‐natal environment dominated the metabolic profile in the male offspring at 4 weeks of age. Offspring exposed to a HFHS environment post‐natally had increased adiposity ( P  < .0001), increased hepatic triacylglycrol accumulation ( P  < .0001), and an altered lipid profile with elevated n ‐6 polyunsaturated fatty acid (PUFA) levels ( P  < .0001) and a reduction in ceramide ( P  < .001) and monounsaturated fatty acid (MUFA) ( P  < .0001). In summary, maternal HFHS diet during gestation affects the hepatic lipid profile in neonates. The pre‐natal exposure becomes less pronounced in young male offspring at 4 weeks of age, where the post‐natal diet has the largest impact.